Trends in Practice Patterns and Clinical Outcomes for Desmoid Tumors: A Large Single‐Institutional Australian Cohort - Joseph Sia; Stephanie Tan; Narayan Mohanakrishnan; Kelvin Yu; Samuel Y. Ngan; Sarat Chander; Jayesh Desai; Jeremy Lewin; Anne Hamilton; Stephen J. Luen; David E. Gyorki; Hayden Snow; et al. (Cancer Medicine)
ABSTRACT Background Desmoid tumors (DT) are rare, locally aggressive neoplasms that affect a young population and have a tendency for recurrence. There is sparse contemporary real‐world data to guide practice for DT. Here, we report on a large cohort of DT patients, describing patterns of care and clinical outcomes. Methods Data on DT patients first seen between 2010 and 2021 were extracted from a prospective database and supplemented with a retrospective review of hospital records. Trends in treatment use were analyzed using the Cochran‐Armitage test. Time‐to‐next intervention (TTNI) was estimated with the Kaplan–Meier method. Imaging response was categorized using the RECIST v1.1 criteria. Results A total of 135 patients, 265 treatment episodes were analyzed. Median follow‐up was 4.3 years. The common tumor sites were abdominal wall (27%), upper limb (20%), lower limb (16%), and intra‐abdominal (15%). Over time, the proportion of patients receiving no upfront treatment was stable (2010–2013: 31%, 2014–2017: 35%, 2018–2021: 29%; p = 0.5), but there was increasing first‐line use of NSAID/tamoxifen (7%, 41%, 47%; p < 0.001), and decreasing first‐line use of radiotherapy (35%, 14%, 4%; p < 0.001) and surgery (28%, 8%, 18%; p < 0.05). At 5 years, the proportion not requiring treatment switch was highest following surgery (72%), radiotherapy (66%), and no upfront therapy (52%). 12% and 5% of patients without treatment achieved partial and complete imaging responses at 2 years. Conclusion We highlight the heterogeneity and trends in DT management over a 12‐year period, affirming the role of active surveillance, radiotherapy, and surgery in selected patients. Medical therapies are evolving and may significantly influence the DT management paradigm.